On the Connotations of аристократ, барин, and буржуа and Their Derivatives in the Russian Language - Frolova, O. Ye (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2017)
Thisarticledescribesthe namesof representativesof differentsocialstrata, whichacquiremetaphoricalcharacterisingmeaningsаристократ (Eng. aristocrat), барин (Eng. barin, gentleman) andбуржуа (Eng. bourgeois). The author analyses semantic interpretations of the direct and figurative meanings of these units in dictionaries, examining personal, abstract nouns, and adjectives. Referring to the Russian National Corpus, she demonstrates how the characterising meaning of adjectives and abstract nouns comes to the fore. The figurative meanings of the derivatives of the Russian words аристократ (Eng. aristocrat), барин (Eng. barin, gentleman) and буржуа (Eng. bourgeois) are formed differently. Among the derivatives of аристократ, only the figurative meaning of the noun bears a negative connotation but not the corresponding adjective or abstract noun. Among the derivatives of the word барин, the figurative meanings of all the three units have negative connotations: the personal noun, the adjective and the abstract noun. In the third group of the буржуа derivatives, there appears the noun буржуй. The use of the adjective буржуазный (Eng. bourgeois) demonstrates a change in connotations throughout time. During the Soviet era, the adjective was used with an ideologically negative colouring, and during the post-Soviet era one can notice a positive connotation. In the early 21st century, the noun буржуазность has both positive and negative connotations though originally it appears to have been a negative one.